Generalized Turán problems for disjoint copies of graphs - Gerbner, Dániel; Methuku, Abhishek; Vizer, Máté (Discrete mathematics, 2019)
Given two graphs H and F, the maximum possible number of copies of H in an F-free graph on n vertices is denoted by ex(n,H,F). We investigate the function ex(n,H,kF), where kF denotes k vertex disjoint copies of a fixed graph F. Our results include cases when F is a complete graph, cycle or a complete bipartite graph.